Chemical profiling and in vitro biological effects of Cardiospermum halicacabum L. (Sapindaceae) aerial parts and seeds for applications in neurodegenerative disorders. (October 2014) - Menichini, Francesco; Losi, Luigi; Bonesi, Marco; Pugliese, Alessandro; Loizzo, Monica R.; Tundis, Rosa
Abstract Cardiospermum halicacabum is widely used in traditional medicine. Previous studies have focused on the aerial parts, while the seeds have been poorly investigated. This work aimed to analyse the chemical composition of extracts from aerial parts and seeds obtained using Naviglio and Soxhlet (PN, PS, and SN, SS, respectively), the inhibitory properties against tyrosinase, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) and the antioxidant effects. PN total extract showed significant anti-tyrosinase activity (IC50 value of 10.8 µg/mL). After partitioning with n-hexane, an HPLC method for analysing chemical constituents was established. Apigenin, luteolin, and apigenin-7-O-glucoside are the predominant constituents. SN n-hexane fraction was the most active inhibitor of BChE (IC50 of 57.9 µg/mL). Gas chromatography-mass spectrometry analysis revealed fatty acids, including eicosanoic acid, methyl 11-eicosenoate and oleic acid, as the major constituents. These findings suggest the potentiality of both seeds and aerial parts of C. halicacabum in the treatment of neurological disorders.